2022
DOI: 10.1002/jeq2.20389
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrients and plant uptake parameters as related to greenhouse gas emissions

Abstract: Fertilizer and water management practices have short-and long-term effects on soil chemical and physical properties and, in turn, greenhouse gas (GHG) emissions. The goal of this 4-yr field study was to establish the relationships between soil properties, agronomic practices, and GHG (CO 2 and N 2 O) emissions under different fertilizer and water table management practices. There were two fertilizer treatments: inorganic fertilizer (IF) and a mix of solid cattle manure and inorganic fertilizer (SCM), combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Significant correlations were noticed between CO 2 emissions and concentrations of SOC (r = 0.622), TN (r = 0.794), C-HA (r = 0.833), C-H (r = 0.844), NH 4 -N (r = 0.921), and NO 3 -N (r = 0.932) (Table 2). Other authors reported earlier that the availability of N and SOM quality are the key factors to C mineralization in soils [17,34]. Changes in N 2 O emissions significantly depended on the fertilization used.…”
Section: Co2 and N2o Emissionsmentioning
confidence: 85%
See 4 more Smart Citations
“…Significant correlations were noticed between CO 2 emissions and concentrations of SOC (r = 0.622), TN (r = 0.794), C-HA (r = 0.833), C-H (r = 0.844), NH 4 -N (r = 0.921), and NO 3 -N (r = 0.932) (Table 2). Other authors reported earlier that the availability of N and SOM quality are the key factors to C mineralization in soils [17,34]. Changes in N 2 O emissions significantly depended on the fertilization used.…”
Section: Co2 and N2o Emissionsmentioning
confidence: 85%
“…Significantly higher contents of SOC (11.28 g kg −1 ) and TN (1.40 g kg −1 ) were found in the soil applied with farmyard manure combined with mineral fertilizer compared to the unfertilized control (Figures 1 and 2), suggesting that organic and mineral fertilization had a beneficial effect on these parameters. Several authors also reported that the SOC levels increase in treatments with farmyard manure [17,30,31] and/or with N inorganic fertilizers [30,32]. This was linked to the amount of additional C and N applied with fertilizers and/or improvements in the crop yields and higher C and N input via rhizodeposition and plant residues [30,33].…”
Section: Soil Organic Carbon and Total Nitrogen In The Soilmentioning
confidence: 98%
See 3 more Smart Citations